Coding and noncoding landscape of extracellular RNA released by human glioma stem cells - Zhiyun Wei; Arsen O. Batagov; Sergio Schinelli; Jintu Wang; Yang Wang; Rachid El Fatimy; Rosalia Rabinovsky; Leonora Balaj; Clark C. Chen; Fred Hochberg; Bob Carter; Xandra O. Breakefield; et al. (Nature Communications, 2017)
While circulating DNA has been extensively explored as a potential cancer biomarker, RNA potential has been overlooked so far. Here the authors present a comprehensive analysis of extracellular RNA secreted by glioblastoma cells that could prove a valuable resource for biomarker discovery and a means of intercellular communication.